2020
DOI: 10.1021/acs.jpcc.0c07010
|View full text |Cite
|
Sign up to set email alerts
|

Switchable Crystal Phase and Orientation of Evaporated Zinc Phthalocyanine Films for Efficient Organic Photovoltaics

Abstract: In photovoltaic cells, increasing the light absorption coefficient enhances the photocurrent and quantum efficiency of the cell. Here, we report an efficient approach that enhances light absorption by changing the crystal phase of an evaporated ZnPc film on indium tin oxide (ITO) substrates. Under thermal treatment (>200 °C), the crystal phase of ZnPc changed from metastable α-ZnPc to stable β-ZnPc. We tested and compared the effects of this phase transition on the donor film of organic photovoltaic (OPV) cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…The experimental crystal structure of β-phase ZnPc 17,41 is adopted for investigation. As for the α phase, since the crystal structure is currently unavailable in the literature, we use the structure of α-phase CuPc 42 as the initial geometry and then replace the Cu atom with a Zn atom while fixing the positions of the other atoms.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental crystal structure of β-phase ZnPc 17,41 is adopted for investigation. As for the α phase, since the crystal structure is currently unavailable in the literature, we use the structure of α-phase CuPc 42 as the initial geometry and then replace the Cu atom with a Zn atom while fixing the positions of the other atoms.…”
Section: Methodsmentioning
confidence: 99%
“…In ZnPc thin films, the microscopic structures are sensitive to the preparation conditions, e.g. , the deposition or annealing temperatures, 12–15 pressures, 16 substrates, 15,17 and film thickness. 15,18,19 So far, several polymorphs of ZnPc have been found in the thin films, 15,18,19 among which the two most common phases are the α and β phases, which are generally distinguished via their X-ray diffraction patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrochemical and spectroelectrochemical properties are important in determining the electronic properties of materials, illuminating the redox mechanism and giving clues about the use of materials in different application areas. It has been reported that MPcs having rich redox and coordination properties can be used as an electrocatalyst in different application areas such as battery, [30] photovoltaic cells, [31] water splitting, [32] reduction of CO 2 , [33] supercapacitors [34] and electrochemical sensors [35] . In addition to their catalytic properties, their color changes during redox reactions depending on the substituted groups of the MPcs allow using in electrochromic applications [36–38] …”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] Metal phthalocyanines (MPcs) are promising organic semiconductors with desirable properties including nontoxicity, high chemical and thermal stabilities, and excellent optical properties. They are used as active layers in various devices, such as organic solar cells, [5][6][7][8] organic transistors, [9][10][11] and gas sensors. [12][13][14] Pcs have extended π-conjugation on their molecular planes and aggregate in the direction of stacking molecular planes, which are favorable for charge transport, owing to their π-π interactions.…”
mentioning
confidence: 99%